2020
DOI: 10.1016/j.virol.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological characterization of SARS-CoV-2 infection among COVID-19 patients

Abstract: Background SARS-CoV-2 is a novel coronavirus and the cause of COVID-19. More than 80% of COVID-19 patients exhibit mild or moderate symptoms. In this study, we investigated the dynamics of viral load and antibodies against SARS-CoV-2 in a longitudinal cohort of COVID-19 patients with severe and mild/moderate diseases. Methods Demographic and clinical information were obtained. Serial samples of blood, nasal and pharyngeal and anal swabs were collected at different time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
(43 reference statements)
2
20
0
Order By: Relevance
“…The influence of seroconversion and antibody levels on the course of the disease remains poorly understood and controversial. 43,[47][48][49] In our study population, all patients developed antibodies against SARS-CoV-2. IgG levels after ECMO initiation did not differ between the three groups and therefore, might not have influenced the clinical course.…”
Section: Discussionmentioning
confidence: 98%
“…The influence of seroconversion and antibody levels on the course of the disease remains poorly understood and controversial. 43,[47][48][49] In our study population, all patients developed antibodies against SARS-CoV-2. IgG levels after ECMO initiation did not differ between the three groups and therefore, might not have influenced the clinical course.…”
Section: Discussionmentioning
confidence: 98%
“…Recent reports have evaluated the neutralizing activity of sera from COVID-19 patients and the results have been controversial. One study suggested that patients rapidly develop nAbs, 21 whereas other studies have indicated that the humoral response 22 and nAb activity 22 – 24 correlate with several parameters, including the severity of the disease, resulting in the absence of nAb activity detection in a significant number of mild symptomatic and ASYs. 25 However, such assumptions were based on a very limited number of observations, as those studies included less than 10 patients with the most severe forms.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, different studies suggest that 14 days after the onset of symptoms is a time period at which serological tests have high sensitivity that is able to replace nucleic acid amplification tests for the effective diagnosis of COVID-19 [ 224 , 225 , 226 ]. In addition, it is important to highlight that it has been demonstrated that more severe cases of COVID-19 have a late humoral response compared to mild/moderate infections [ 227 ], as well as high antibody titers have been shown to be associated with the severity of the disease [ 228 ]. Similar behavior was also found when neutralizing antibody titers were analyzed, where it was reported that asymptomatic patients do not produce a prolonged response [ 229 ], while patients with moderate to moderate symptoms produced robust responses against the SARS-CoV-2 spike protein [ 230 ].…”
Section: Nucleic Acid-based Tests and Serological Tests: Practicalmentioning
confidence: 99%
“…Similar behavior was also found when neutralizing antibody titers were analyzed, where it was reported that asymptomatic patients do not produce a prolonged response [ 229 ], while patients with moderate to moderate symptoms produced robust responses against the SARS-CoV-2 spike protein [ 230 ]. Li et al [ 228 ] observed the production of antibodies in adults reached their peak at 17 days after the onset of symptoms and then remained at a relatively high level for up to 50 days. Similar behavior was also reported by Roarty et al [ 231 ], who demonstrated that antibody titers in children previously exposed to SARS-CoV-2 remained detectable up to 62 days after the onset of symptoms.…”
Section: Nucleic Acid-based Tests and Serological Tests: Practicalmentioning
confidence: 99%